A conceptual framework for wealth maximization: literacy and planning embedded model - D Sundarasen, Sheela Devi; Rahman, Muhammad Sabbir; Rajagopalan, Usha (Canadian Center of Science and Education, 2014)
The aim of this paper is to develop a conceptual framework for wealth maximization. The paper deﬁnes and presents conclusive issues pertaining to financial literacy, financial planning and wealth maximization and expect to paradigm a conceptual framework for a prospective investigation. The research attempts to ascertain the significance of demography, perception towards money and parental role on financial literacy, financial planning and wealth maximization. Further research is obligatory to validate empirically the framework through systematic investigations and to assess its viability as a wealth maximization model. It is envisioned that the creation of awareness and transfer of financial literacy and planning to individuals will liberate the government to delve on macro level issues for economic prosperity. The theme is original and positions itself as the beginning stream of financial literacy and planning research, ultimately crafting foundational contribution to wealth maximization.